Rancang Bangun Alat Ukur Kualitas Air Sanitasi Berbasis ESP32-C6 dan Internet of Things - Nur Kholis Nafis; Julman Notatema Waruwu; Aisyah Putri Harmelia; Asri Sarassufi Aisah; Daffa Maulana Kindi A.L; Purba M. Ahla Kurniawan; Muhammad Reynaldi Ilham; Bayu Widodo; Mamat Rahmat (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Sanitation water quality is one of the important factors affecting public health. Conventional water quality monitoring generally requires laboratory testing, which is relatively time-consuming, costly, and unable to provide real-time information. This study aims to design and develop an Internet of Things (IoT)-based sanitation water quality monitoring device using an ESP32-C6 microcontroller integrated with pH, total dissolved solids (TDS), turbidity, and temperature sensors. The research method consisted of system design, hardware implementation, sensor accuracy testing, and stability testing through repeated measurements. Accuracy testing was conducted by comparing sensor readings with reference measuring instruments, while stability testing was evaluated using standard deviation and precision (%RSD) values. The results showed that the pH sensor had an error rate of 0.24% and the temperature sensor had an error rate of 2.51%, where as the TDS sensor exhibited an error rate of 16.92%. Stability testing indicated that all sensors produced relatively small measurement variations, with precision values ranging from 0% to 2.53%. Testing on tap water, well water, and river water samples demonstrated that the system was able to distinguish water quality characteristics based on the measured parameters. The results indicate that the developed system is capable of performing real-time water quality monitoring and generating consistent measurement data during repeated observations. This study may serve as a basis for the further development of IoT-based sanitation water quality monitoring systems through improved sensor accuracy and the inclusion of additional water quality parameters in future research.